Reflections about the geologic trails in Slovenia - Rajko Pavlovec (Geologija, 2002)
In Slovenia exist several longer or shorter geologic trails. The author prefers shorter, but better prepared geologic trails. Such trails are more interesting to individuals, and they are useful also for school excursions and natural science days.